Recent publications on Sarajevo - Gudelj, Jasenka (2011)
Rewiew of: Ibrahim Krzović, Arhitektura secesije u Bosni i Hercegovini, Sarajevo, Sarajevo publishing, 2004., 254 str. ISBN 9958-21-305-2 Mehmed Hrasnica, Arhitekt Josip Pospišl – život i djelo, Sarajevo, Arhitektonski fakultet, 2002., 273 str. ISBN 9958-9706-6-X Robert J. Donia, Sarajevo: A Biography, London, Hurst & Company, 2006., 435 str. ISBN 1-85065-765-3 Laura Cipollini, Sarajevo, u: Città e memoria: Beirut, Berlin, Sarajevo, ur. Mazen Haidar, Milano, Bruno Mondadori, 2006., 97-161 str. ISBN 88-424-9237-x
ENG